Literary Translation Teaching: Methodological and Formative Proposals - Ortiz García, Javier (Estudios de Traducción, 2016)
This essay deals with the teaching of literary translation in a university context from a methodological perspective. The study is firstly framed within the PACTE principles regarding the acquisition of translation competences; then, we proceed to analyze and discuss three relevant aspects to the practice and the teaching of literary translation: i) the approach to style; ii) the explicit differentiation between dialogue and narration; and iii) some issues related to the literary translation market. In order to achieve the proposed objectives, the essay is widely illustrated with translation examples taken from the classroom.